Frequency of Breast Ultrasound Findings in patients presenting with Mastalgia - Eisha Tahir, Shumaila Jabeen, Omar Altaf, Sadaf Ishaque, Zafar Rafique (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of different Mastalgia findings on breast ultrasound. Methodology: This was a prospective, cross-sectional study, conducted at Radiology department of Shalamar Hospital, Lahore from 1st September 2021 to 29 February 2022. This study includes all patients having breast pain with at least one month of duration presenting to OPD or breast clinic of Shalamar Hospital. All patients were referred breast ultrasound after taking history and examination. The results of their breast ultrasound were recorded on Performa. Results: A total of 95 female patients of age above 18 years were included. Mean age of patients, was 35.4 ±10.7years. Mean duration of breast pain was 4.27±3.9 months. The ultrasound findings which showed benign pathologies include, Benign lesion 10(10.5%), Fibroadenoma 13(13.7 %), Simple cyst 8(8.4%), and Duct ectasia 7(7.4%). Abscess in the breast also diagnosed in 5(5.3%) patient. 52 (54.7%) females had normal breast ultrasound from which 37(71.2%) were with cyclic pain and 15(28.8%) were with non cyclic pain. Conclusion: Females presenting with complaint of breast pain have different ultrasound findings. In the majority of patient, there was no abnormality found (normal ultrasound). Ultrasound helps to determine the cause of breast pain so that in case of any disease, specific treatment or further investigation advised and normal report provides reassurance to the patients by reducing fear and anxiety. Key words: Breast ultrasound, Mastalgia, breast pain